2009
DOI: 10.1007/s00109-009-0564-y
|View full text |Cite
|
Sign up to set email alerts
|

Contact system activation in severe infectious diseases

Abstract: Hemostasis is a sensitive and tightly regulated process, involving vascular endothelium and blood cells, as well as factors of the coagulation and fibrinolytic cascades. In severe and invasive infectious diseases, the equilibrium between the procoagulant and anticoagulant status of the host may change dramatically and can induce life-threatening complications. A growing body of evidence suggests that the contact system, also known as the intrinsic pathway of coagulation or kallikrein/kinin system, participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 62 publications
1
57
2
Order By: Relevance
“…Involved in almost any kind of infl ammation, the kinins induce a secondary release of pro-infl ammatory mediators such as nitric oxide, prostaglandins and cytokines by a variety of effector cells (Blais et al , 2000 ;Moreau et al , 2005 ). The activation of the kininforming system has been suggested to constitute an important part of the human host defense against microbial infections (Oehmcke and Herwald , 2010 ). However, some kinin-exerted effects can be considered as ' benefi cial ' to pathogens, such as the enhancement of vascular permeability, which causes the infl ow of plasma and facilitates the availability of nutrients and the spreading the pathogen within the host organism (Potempa and Pike , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Involved in almost any kind of infl ammation, the kinins induce a secondary release of pro-infl ammatory mediators such as nitric oxide, prostaglandins and cytokines by a variety of effector cells (Blais et al , 2000 ;Moreau et al , 2005 ). The activation of the kininforming system has been suggested to constitute an important part of the human host defense against microbial infections (Oehmcke and Herwald , 2010 ). However, some kinin-exerted effects can be considered as ' benefi cial ' to pathogens, such as the enhancement of vascular permeability, which causes the infl ow of plasma and facilitates the availability of nutrients and the spreading the pathogen within the host organism (Potempa and Pike , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The KKS participates in a number of homeostatic and host-defense functions, including the innate immune response to invading microorganisms. 4,5 KKS components assemble and are activated on the surface of microorganisms, generating antimicrobial peptides and contributing to complement activation. 5 The capacity of the KKS to bind to surfaces is also important for initiating blood coagulation in vitro in the activated partial thromboplastin time assay (aPTT) used in clinical practice.…”
Section: David Gailani Vanderbilt Universitymentioning
confidence: 99%
“…4,5 KKS components assemble and are activated on the surface of microorganisms, generating antimicrobial peptides and contributing to complement activation. 5 The capacity of the KKS to bind to surfaces is also important for initiating blood coagulation in vitro in the activated partial thromboplastin time assay (aPTT) used in clinical practice. In the aPTT, anionic substances such as purified earths trigger reciprocal activation of factor XII and prekallikrein in a process called contact activation.…”
Section: David Gailani Vanderbilt Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…Heiko Herwald at Lund University has been studying activation of the kallikein/kinin or contact system by S. aureus and GAS toxins and its role in the severe manifestations of sepsis such as hypotension and vascular leakage. From these data, it is suggested that blockage of kinin receptors or administration of C1 inhibitor, itself a regulator of the contact system, could have beneficial effects on mortality and lung injury induced by Gram-positive bacterial infection [12]. Profound alterations in the microcirculation, a byproduct of localized leukocyte adhesion and activation coupled to the systemic inflammatory response, are also manifested in Grampositive bacterial sepsis.…”
mentioning
confidence: 99%